Retained wooden foreign body in groin in a child: A case report and review of literature - Enono Yhoshu; Gyanendra Chaudhary; Manish Kumar Gupta (Wolters Kluwer Medknow Publications, 2020)
Wooden foreign body (WFB) injuries in children are common. They may report with acute presentation or be delayed as retained foreign body giving rise to complications. Cases with superficial skin penetration by these foreign bodies and acute presentation may be convenient to diagnose and remove. However, localising deeply impacted and chronically retained WFB is challenging, as they are usually not radiopaque and have a tendency to move deeper into the surrounding soft tissues with time. Foreign body retained for prolonged duration may present with either cellulitis, deep tissue infections, sinus, restriction of joint movements, necrotising fasciitis, osteomyelitis or tumour-like mass. We present an 8-year-old boy with discharging sinuses in the right iliac fossa and medial aspect of the right upper thigh, due to an impacted WFB for 3 months. Prompt radiological imaging and surgical removal helped him recover completely.